Anti-fungal Resistance Threats in Dermatophytosis : A Literature Review - Ida Ayu Made Niki Putri Ashrita; Lina Damayanti (Faculty of Medicine, Universitas Airlangga, 2026)
Background: In recent years, antifungal resistance in dermatophytosis has escalated, observed not only in the endemic regions of India but also across East Asia, the Americas, and Europe. The inappropriate use of antifungal drugs has the potential to drive the development of drug resistance. Purpose: This literature review aims to present an overview of antifungal resistance in dermatophytosis and to examine the mechanisms underlying resistance to the principal antifungal classes. Review: The reported mechanisms of terbinafine resistance include point mutations in the squalene epoxidase (SQLE) gene, most commonly the F397L and L393F substitutions. Reduced azole susceptibility appears to be mediated predominantly by overexpression of genes encoding ATP-binding cassette (ABC) transporters, although CYP51B overexpression has been implicated in Trichophyton indotineae, suggesting that mechanisms differ between species. Griseofulvin resistance has been associated with mutations in the TUB2 gene encoding β-tubulin, together with efflux-mediated mechanisms analogous to those described for azoles. Conclusion: Most reports identify terbinafine resistance as the principal cause of treatment failure. Although reported cases and studies of azole resistance in dermatophytes remain limited, the documented increase in itraconazole minimum inhibitory concentrations (MICs) among terbinafine-resistant strains, together with the similarities between Indonesia and India in economic development, population density, geography, and hygiene levels, warrants vigilance toward this phenomenon.